¿La democratización en contra de los trabajadores? La CUT, el movimiento sindical y el dilema de la transición pactada en Chile - Sebastián Osorio; Franck Gaudichaud (Les Cahiers de Framespa)
The present (this) article envisions the democratisation process in Chile through the prism of one essential but little-examined factor in transition studies: trade-unionism. Whilst questioning the real import of the "pact-driven transition" towards democracy, as well as the content of the neo-liberal project implemented by the first post-dictatorship government in matters relating to work and employment, this study seeks to explain how the political orientations of the CUT ("United Workers’ Federation") under Patricio Alwin’s presidency may have played a crucial role in the failure of the trade union strategy of the "Concertation" parties and further of the workers’ mobilisations in the following years.